Implementasi Differentiated Instruction dalam Pendidikan Agama Kristen untuk Meningkatkan Regulasi Emosi Peserta Didik - Jhonnedy Kolang Nauli Simatupang; Hizkia Lumban Tungkup (Jurnal Kala Nea, 2025)
The implementation of Differentiated Instruction (DI) in Christian Religious Education aims to help students overcome difficulties in managing their emotions through an approach that adjusts teaching methods and the emotional needs of individuals. This study uses a qualitative approach with a literature review to examine how DI can be applied in the context of Christian religious education to support the emotional development of students. Based on the literature review, DI, which includes adjustments in content, process, product, and learning environment, is effective in creating an inclusive and responsive learning experience that meets the needs of students. Using Bible stories and applying moral values such as love, forgiveness, and patience, DI also provides space for students to better understand and manage their emotions. This study demonstrates that by adapting teaching approaches to the emotional needs of students, DI not only supports academic achievement but also helps them manage their feelings and develop better character.